A Study to Assess the Utility of Cell Block Morphology and Immuno-Cytochemistry For Improving the Pre-Operative Diagnosis of Nodular Thyroid Lesions - Mishra, Shruti; S, Kishore Kumar; Das, Saumik; Samaddar, Aparajita; Das, Nandini; Nag, Dipanwita (Annals of Pathology and Laboratory Medicine, 2020)
Background: Thyroid nodules are quite common in the general population of India with increasing incidence of malignancy worldwide. Fine Needle Aspiration [FNA] has been the primary modality of pre-operative diagnosis of such lesions till date. But it has got its own share of fallacies and pit-falls. Cell-block [CB] can be done in the same sitting and it gives the advantage of architectural assessment with easy subjectivity to immuno-cytochemical [ICC] staining. Material and methods: FNA was done in all patients and CB was prepared by formalin method. ICC stains were used in cases with provisional diagnosis of malignancy and in all follicular neoplasm cases. SPSS v.20 was used for analysis. Sensitivity and specificity of cell block was calculated. Diagnostic correlation of both FNA and CB with respect to histopathological examination was done by using student t-test with confidence interval of 95%. Results: CB showed a correlation coefficient of 0.704 and a p value of 0.0001while FNA showed a correlation coefficient of .464 and a p-value of .001. So, CB showed a strong positive correlation and a high statistical significance. Cell block helped in diagnosing almost all the cases showing discordance in FNA except that of papillary carcinoma where the cellular yield was poor due to cystic degeneration. Sensitivity of cell block was 89.5% and Specificity was 96.9%. Conclusions: Cell block is definitely a good ancillary examination for thyroid nodular lesions in addition to FNA. It should be routinely performed in all thyroid cases as it improves the diagnostic yield and accuracy of cytological diagnosis.